PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN KORAN HARIAN SUARA MERDEKA (Studi Empiris pada Pelanggan Koran Harian Suara Merdeka di Kota Semarang) - Lenny Dwi Damayanti, 13.05.51.0041; Widyasari, Suzy (Students Journal of Economic and Management, 2017)
Newspaper is one form of media that has existed since hundreds of years. Newspapers have been attached to the soul of society as a necessity that is difficult to replace. Currently the development of the mass media increasingly stringent demands of companies should have the right competitive strategy so that their products can survive and remain in demand by customers. Through appropriate pricing strategy, the quality of high-quality products and a good brand image is the effort in maintaining customer satisfaction. The population in this study is the customers Suara Merdeka daily newspaper in Semarang in 2015 as many as 100 people. The sampling technique used purposive sampling. The analysis technique used is multiple regression analysis. Based on the results of the study show that the product quality, price and brand image had positive and significant influence on customer satisfaction Suara Merdeka daily newspaper in Semarang. And in this study the image of the brand has a dominant influence on customer satisfaction. Keyword: Product Quality, Price, Brand Image, Customer Satisfaction